Cloud Enabled Machine Learning Framework for Medicine System - Asalkar Sharayu; Roshani Dhule; Aishwarya Ghulme; Rutuja Sabale; Jaishri R. Shilpakar (International Journal of Mobile Computing Technology, 2025)
The Medicine Generic App is a cutting-edge mobile application designed to empower users with information about generic medications. Given the rising expenses of healthcare and prescription medications, this app acts as a useful resource for consumers to make informed decisions regarding their medication options. The Medicine Generic App aims to promote generic drug usage, reduce healthcare costs, and improve medication management for users. By providing detailed information and price transparency, this app enables individuals to make informed choices regarding their healthcare, resulting in improved health outcomes and cost savings. This study outlines the key features and advantages of the Medicine Generic App, emphasizing its potential to benefit healthcare consumers and encouraging the use of affordable generic medications.
Keywords: Cloud computing; Health cloud; Privacy; machine learning model; security; virtual networking